Using children as participants in paediatric skills objective structured clinical examination who give feedback. (29th September 2015) - Fertleman, C; Prentice, P; Clarke, B
Abstract : Background: Paediatricians need to effectively communicate with children when taking histories, making and explaining diagnoses, and involving children in management plans. This might additionally include teaching a child a practical skill, for example how to take a particular medication. All trainees need to be proficient and confident when communicating with a child alone, since this is often valuable in paediatric practice. Aim: To devise simple scenarios that children between the ages of 8 and 12 years, who could read and role play, could undertake with paediatric trainees before their MRCPCHclinical examinations. This was to: provide a novel way to enhance paediatric training and examination practice; further involve children and their feedback in communication teaching. Method: The authors devised simple scenarios that children between the ages of 8 and 12 years, who could read and role play, could undertake with paediatric trainees before their MRCPCH clinical examinations. The children were interviewed in the absence of their parents so that feedback was solely child-led. Scenarios included: bedwetting, constipation and child abuse scenarios (communication skills); Epipen training, peak flow meter and volumatic device use scenarios (practical skills). The children were taught how to give effective feedback using Pendleton's rules for good feedback. Results: The children were able to give appropriate and helpful comments, which trainees found very useful. All six scenarios with 3 child actors were videoed and the material was then shown to the paediatric trainees to further enhance learning. This material has been subsequently used in teaching with other paediatric trainees and medical students. Conclusions: It is important for trainees to reflect and understand how children perceive information which is given to them and how they want information relayed. This applies to children seen for the first time in an outpatient appointment, as well as those with chronic disease. The children enjoyed the role plays and the opportunity to be listened to and engaged in communication scenarios. The authors feel this is a useful tool, to be further developed and used more widely. This should improve trainees' communication with children and emphasise aspects of communication that children feel are most important.